Metal free C–H functionalization of diazines and related heteroarenes with organoboron species and its application in the synthesis of a CDK inhibitor, meriolin 1. Issue 18 (18th April 2016) - Thatikonda, Thanusha; Singh, Umed; Ambala, Srinivas; Vishwakarma, Ram A.; Singh, Parvinder Pal
Abstract : Here, we report a metal-free cross-coupling reaction of diazines and related heteroarenes with organoboron species. Abstract : Here, we report a metal-free cross-coupling reaction of diazines and related heteroarenes with organoboron species via C–H functionalization. The optimized conditions represent a metal-free method for the activation of aryl/heteroarylboronic acids, which undergo coupling with diazines and related heteroarenes. Optimized conditions also find application in the synthesis of a pyrimidine-based potent CDK inhibitor, meriolin 1 .